FTIR spectra analysis of sediment influenced by acid mine drainage - Singovszka, Eva; Balintova, Magdalena (International Conference “Environmental Engineering”, 2017)
The contamination of aquatic and terrestrial ecosystems with heavy metals and other mining chemicals have been major environmental problems in many mining areas of the world. Industrial wastes, geochemical structure and metals mining form a potential source of metal contaminants in the aquatic environment especially in sediment. In Slovak Republic there are some localities with existing acid mine drainage (AMD) generation conditions. The most critical values were observed in the abandoned deposit Smolnik. Waters from the earth surface penetrated the mine and they are enriched with metals and their pH values decreased. Increasing of pH after their mixing with surface water has negative influence on accumulation of pollutants in sediment. The aim of this paper is to investigate the use of Fourier transform infrared (FTIR) transmittance spectroscopy for identification of changes of functions group in the sediment composition influenced by acid mine drainage. Chemical parameters of sediment quality were studied also by X-ray fluorescence spectrometry (XRF).